Depression, anxiety, and stress during the COVID-19 pandemic: comparison among higher education students in four countries in the Asia-Pacific region - Jiang, N. (Institute for Population and Social Research, Mahidol University, 2021)
The global COVID-19 pandemic is affecting the health of individuals and leading to psychological problems. Students in higher education who are graduating, facing online learning challenges, and future job opportunities are among the most at-risk group for psychological issues. Due to the new normal of the COVID-19 pandemic, limited studies have been conducted concerning the mental health of students, especially in the Asia-Pacific region. Therefore, this study aimed to assess student's depression, anxiety, and stress status in four countries in the Asia Pacific region, namely, Malaysia, Indonesia, Thailand, and China. This study employed a quantitative research design with a pool of 1,195 student participants. The DASS-21 questionnaire was used for data collection through an online platform to measure the severity of depression, anxiety, and stress. Descriptive statistics were conducted to achieve the research objectives, and all reliability values were reported greater than 0.70. Findings revealed that up to 38 of the students reported mild or moderate depression, anxiety, and stress, while 20.5 reported severe or extremely severe anxiety. Overall, anxiety was reported to be the most significant problem among the students, followed by depression and stress. Students are at risk of mental health challenges during the coronavirus pandemic, likely due to unexpected life changes. This study contributes an overview report of students' mental health problems and discusses the support and services in preventing students' psychological problems. The comprehensive discussion has provided scientific information and suggestion to policymakers in maintaining the student academic and welfare. © 2021. All Rights Reserved.